ASSESSING GERIATRIC DISABILITY AND ITS ASSOCIATED FACTORS AMONG THE URBAN POPULATION OF TAMIL NADU, INDIA: A PREVALENCE STUDY - Kandasamy, Premanandh; Mahendran, Rajalakshmi; Radhakrishnan, Shankar (Journal of Public Health Research and Community Health Development, 2023)
Background: Disability among the geriatric population is a major health issue. Assessment of disability among the elderly population is useful in terms of identifying the needs, setting priorities, and allocating resources. Purpose: To assess the disability level among the geriatric population and to identify factors associated with disability. Methods: Used prevalence study among 384 participants in the age group between 60 and 80 years. Eligible households for interview were selected using systematic random sampling (every 5th household). Trained interviewers carried out the study by direct interviews at the individuals' residences using the WHODAS 2.0 questionnaire. Individuals with normal cognitive status (abbreviated mental test score >6) were included in the study. In determining the overall level of disability, the International Classification of Functioning scale were used: extreme disability (96 to 100%), severe disability (50 to 95%), moderate disability (25 to 49%), mild disability (5 to 24%) and no disability (0 to 4%). Results: Around 32.8% of the study population reported no disability, 40.9% disability was reported by most, and moderate level of disability 24.0%. Analysis of the factors associated with disability level showed the existence of significant relationships between disability score >24 and factors like age, marital status, family type, living arrangement and, physical activity of more than 150 hours per week. Conclusion: Higher disability rate was noted among the elderly in the study population. Increasing age, single member /nuclear family, divorced/widowed individuals, and inadequate physical activity were the factors significantly associated with increasing disability level.